ABCA7*V1599M variant in 5xFAD mice mediates differences in amyloid‐beta pathology and reactive gliosis. (20th December 2022) - Butler, Claire Ann; Javonillo, Dominic I; Houchin, Lauren A; Kawauchi, Shimako; Phan, Jimmy; Da Cunha, Celia; Tran, Katelynn; Milinkeviciute, Giedre; Tenner, Andrea J; LaFerla, Frank; MacGregor, Grant R; Green, Kim N
Abstract: Background: In several large genome‐wide association studies (GWAS), genetic polymorphisms of ATP‐binding cassette transporter subfamily A member 7 ( Abca7 ) have been identified as a risk factor for late‐onset Alzheimer's Disease (LOAD). ABCA7 is a member of a family of ATP‐binding cassette (ABC) transporters and functions as a transmembrane protein mediating the release of cholesterols and phospholipids from cellular membranes. Previous studies have also proposed its role in mediating phagocytic clearance of amyloid beta (Aβ) oligomers within macrophages in the brain. Method: To study the effects of ABCA7 on the development of AD relevant pathologies we introduced an equivalent coding sequence change that has been identified as a risk variant for LOAD (V1613M) into the C57BL/6 mouse genome using CRISPR/Cas9 (V1599M). We set out to characterize the ABCA7 V1599M variant and investigate its impact on AD pathology when crossed with 5xFAD transgenic mice, generating four distinct groups: WT, ABCA7 V1599M homozygous, 5xFAD, and 5xFAD x ABCA7 V1599M homozygous. Characterization was performed using histological staining and biochemical approaches. Result: Coronal brain sections from 4‐month‐old mice (n=5‐6 mice/sex/genotype) revealed significantly reduced burden of dense‐core Aβ plaques in confocal images of both subiculum and visual cortical regions of 5xFAD x ABCA7 V1599M mice compared to 5xFAD mice characterized by reduced Thioflavin‐S staining. Biochemical analysis mirrored these findings and demonstrated reductions of both soluble and insoluble Aβ40 and Aβ42 levels within these same brain regions. To examine reactive gliosis to plaque burden, we immuno‐stained for ionized calcium binding adaptor molecule 1 (IBA1) and glial fibrillary protein (GFAP) to visualize microglia and reactive astrocytes, respectively. Confocal analysis revealed reduced densities of both IBA1 + microglia and GFAP + reactive astrocytes within subiculum and cortical regions of 5xFAD x ABCA7 V1599M mice compared to 5xFAD mice. We also found reduced plaque‐associated neuritic damage in 5xFAD x ABCA7 V1599M mice upon immuno‐staining for lysosome‐associated membrane glycoprotein 1 (LAMP1) to examine neuritic dystrophy Conclusion: Together, these results characterize the effects of the Abca7 em1Aduci allele and its ABCA7 V1599M missense mutation on 5xFAD‐mediated pathology, specifically in Aβ plaque development, glial morphology, and neuritic damage.